Handling Students’ Social Problems in the 4.0 Industrial Revolution Era - Subianto Karoso; Abdul Nadjib; Husnul Yaqin; Nikmah Suyandari; Eko Lianto Rihardi; Irfan Nurdiansyah (STAI Hubbulwathan Duri, 2022)
The Industrial Revolution 4.0 is marked by advances in information technology so that the ease and speed of receiving information without any filtering make the vulnerability of problems arise among students. Youth or students are considered as future leaders. Today, many of them are involved in disciplinary matters and some worrying social problems. Some are interested in juvenile crime leading to criminal acts. Others were engaged in absenteeism from school and bullying. Several factors contribute to social problems, such as lack of parental love and attention, negative influence from peer groups, lack of religious education, and others. Discipline problems are the main factors inhibiting student academic achievement. Therefore, this study tries to raise the Handling of Student Social Problems in the Industrial Revolution 4.0 era. The method used in this research is descriptive qualitative with data collection sources based on library research, namely from journals, books or other sources related to handling student social problems. The results showed that the social problems of students in the school environment that arose in the 4.0 industrial revolution era were divided into two, namely internal social problems that arise from the students themselves, namely difficulties in getting along and introverted personalities and external factors or social problems that come from outside the students, namely bullying. And coercion by parents. In this study, the author also explains the causal factors and how to overcome these internal and external social problems.